A study on metaphors in English advertising slogans for food and beverage. / Lưu Thị Phương Thảo; NHDKH Dr. Tran Thi Thu Hien - Lưu, Thị Phương Thảo
The choice of this topic is prompted by my interest of metaphors, especially metaphors used in English advertising slogans for food and beverage. The study aims to explore metaphors used in food and beverage slogans favored to advertisers and popular with customers. There is a variety of theories on metaphor and its use in advertisements, but this study is mainly based on the work of Lakoff and Johnson where metaphor is seen as a conceptual process that people use to understand and categorize the world. Therefore, forty slogans from international food and beverage brands such as: Coca-cola, Burger king, Mc Donald, Pepsi and other famous ones are classified into types based on Lakoff and Johnson’s classification, an analysis of the target domain, source domain and metaphor concept is conducted. By combining descriptive and qualitative methods, the study treats the common uses of metaphor in food and beverage advertising slogans. From the findings and analysis, we realize that conceptual metaphor plays an important part in advertising slogans in which ontological metaphor, orientational metaphor and structural metaphor are the most commonly used. The study is very useful for learning and teaching foreign language that helps teachers provide students with valuable ways of understanding through metaphor, since then students can learn and perceive language through practising and applying metaphors. The study can also help advertisers use metaphors in designing and writing advertising slogans and advertisements effectively.